AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE POEM OF MARGARET ATWOOD “ A SAD CHILD” - M. Asrul Hasby (Sinar Lima, 2025)
This study aimed to identify the figurative language used in the poem A Sad Child by Margaret Atwood. The study employed a qualitative method with a focus on analyzing the types of figurative language based on Perrine's theory. The primary data for this research was derived from the poem itself, complemented by secondary data from literary sources. The findings revealed that the poem utilized various types of figurative language, including metaphor, personification, symbolism, irony, imagery, and allegory. These elements collectively conveyed themes of sadness, loss of self-confidence, and the complexities of childhood emotions. This research highlighted how figurative language enhanced the emotional depth and empathetic impact of the poem. It provided valuable insights for readers in understanding the nuances of figurative language and its role in poetry.